The Festivities and the Inauguration of the Military Cycle in the Roman Calendar: an analysis of Equirria and Tubilustria in the Fasti of Ovid (1st century AD): As Festividades e a Inauguração do Ciclo Militar no Calendário Romano: uma análise das Equírrias e Tubilústrias nos Fastos de Ovídio (Séc. I d.C.) (Revista de História da UEG (REVHIST), 2023)
Composed in elegiac couplets, Ovid's Fasti provide valuable information about the rites and festivities in ancient Rome which are, conventionally, divided between the festivities of the agrarian cycle, civic festivities and those of a warlike nature. Understood as a didactic poem, the text mixes technical information with amusing mythological excursus by portraying the etiology of Roman festivals, temples and rituals. This article focuses on the issue of festivities, especially those of the martial cycle (Equirria and Tubilustria) which put in evidence the ritual devices of preparation for war, in addition to problematizing Ovid's poetic constructions in the description of these religious ceremonies.Keywords: Festivities. Roman calendar. War Cycle. Ovid. Equirria. Tubilustria.